Survival and Growth of Pangasianodon hypopthalmus Fed with Moringa oleifera Enriched Pellets and Reared in Tank With Aquaponic System and Dark Condition - Windarti Windarti; Sofyan Husein Siregar; Asmika Harnalin Simarmata; Joko Samiaji (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Pangasianodon hypophthalmus grows well in a dark tank completed with an aquaponic system. To improve the growth, a feed supplement made from Moringa oleifera might be used as it is rich in protein, vitamins A, B, C, and minerals. To understand the effect of M.oleifera addition in the feed of fish, research has been conducted in June-July 2022. M. oleifera leaves were dried and powdered and then mixed with commercial fish feed pellets. There were 4 treatments of M. oleifera dosages, namely T0 (no M. oleifera), T1 (10 g/kg), T2 (15 g/kg), and T3 (20 g/kg). The fish was reared in a 100L container (30 fishes/tank, around 4 g BW and 8 cm TL), covered with a dark-colored tarp, and completed with the aquaponic system using Ipomoea aquatica. The feed was given 2 times/day, ad libitum. Samplings were conducted once/10 days, for 40 days. Results showed that the survival of fish in all treatments was 93.3 – 98.89%. The growth of fish, however, was different. There was no difference in fish body weight (BW), total length (TL), and specific growth rate (SGR) of fish fed with Moringa, they were around 23.5 g BW, 5.8 cm TL, and 4.3 cm SGR respectively. While those of the control fish were 13.0 g BW, 4.23 cm TL, and 2.89% per day SGR respectively. The fish that was fed with Moringa-enriched pellets showed the highest Feed Efficiency (90.42-97.46%) and the lowest FCR (1.03 – 1.11). While in the fish that was not fed with Moringa showed the lowest FE (75.48%) and the highest FCR (1.33%). Data obtained indicate that Moringa positively improves the growth of fish as well as improving feed efficiency